A brittle star is born: Ontogeny of luminous capabilities in Amphiura filiformis. - Constance Coubris; Laurent Duchatelet; Sam Dupont; Jérôme Mallefet (PLoS ONE)
Bioluminescence is the production of visible light by living organisms thanks to a chemical reaction, implying the oxidation of a substrate called luciferin catalyzed by an enzyme, the luciferase. The luminous brittle star Amphiura filiformis depends on coelenterazine (i.e., the most widespread luciferin in marine ecosystems) and a luciferase homologous to the cnidarian Renilla luciferase to produce blue flashes in the arm's spine. Only a few studies have focused on the ontogenic apparitions of bioluminescence in marine organisms. Like most ophiuroids, A. filiformis displays planktonic ophiopluteus larvae for which the ability to produce light was not investigated. This study aims to document the apparition of the luminous capabilities of this species during its ontogenic development, from the egg to settlement. Through biochemical assays, pharmacological stimulation, and Renilla-like luciferase immunohistological detection across different developing stages, we pointed out the emergence of the luminous capabilities after the ophiopluteus larval metamorphosis into a juvenile. In conclusion, we demonstrated that the larval pelagic stage of A. filiformis is not bioluminescent compared to juveniles and adults.